Challenges in Implementing Participatory Poverty Research with Children: Methodological and Ethical Reflections for Practice in Japan - Sheng Chen (Asean Social Work Journal, 2026)
This study examines the challenges of implementing participatory poverty research with children. Conventional poverty research has largely been led by adult researchers, and the concept of child poverty has been constructed without clarifying how children perceive poverty. Although Japanese scholars have recently begun calling for incorporating children’s perspectives into poverty research, little progress has been made in developing empirical methodologies. To address this issue, in addition to the “expert knowledge” of researchers, participatory research in which children take an active role as participants is important. However, due to practical difficulties in implementation, participatory poverty research in Japan remains limited, with most efforts focused on adults and little to no involvement of children. This study draws on participatory poverty research with children in the UK, which has a rich history of such research. Using a framework developed from participatory poverty research with adults in Japan, this study examines how the challenges identified in that framework are manifested and addressed in UK studies with children. Through this analysis, the study aims to clarify specific methodological and ethical considerations for future practice in Japan.